A poly‐superellipsoid‐based approach on particle morphology for DEM modeling of granular media - Zhao, Shiwei; Zhao, Jidong (International journal for numerical and analytical methods in geomechanics, 2019)
Summary Particle morphology plays a key role in affecting physical and mechanical behaviors of granular media. While various mathematical approaches and shape descriptors have been proposed to describe the morphological properties of granular particles, it remains a challenge to effectively incorporate them for efficient discrete modeling of granular materials. This study presents a new poly‐superellipsoid‐based approach for three‐dimensional discrete element method (DEM) modeling of non‐spherical convex particles. A uniform mathematical description of 3D poly‐superellipsoidal surface is employed to represent a realistic granular particle, which is shown to be versatile and effective in reproducing a wide range of shape features (including elongation, flatness, angularity, and asymmetry) for real particles in nature. A novel optimization approach based on hybrid Levenberg‐Marquardt (LM) and Gilbert‐Johnson‐Keerthi (GJK) algorithms is further developed for efficient and robust contact detection in DEM simulation of poly‐superellipsoidal assemblies. Simulations of granular packing and triaxial compression tests show that the proposed approach is generally robust and efficient for both dynamic and quasistatic modeling of granular media.